Solutions for a Class of Nonperiodic Superquadratic Hamiltonian Elliptic Systems Involving Gradient Terms - Shengzhong Duan; Xian Wu (Discrete Dynamics in Nature and Society)
In the present paper, we consider the following Hamiltonian elliptic system HES: -Δu+bx·∇u+Vxu=Hvx,u,v,  x∈RN, -Δv-bx·∇v+Vxv=Hux,u,v,  x∈RN. A new existence result of nontrivial solutions is obtained for the system HES via variational methods for strongly indefinite problems, which generalizes some known results in the literatures.